Reliability of coeliac and superior mesenteric artery origin level in lumbosacral transitional vertebrae detection and vertebral numbering - BALTACIOĞLU, FEYYAZ; BIYIKLI, ERHAN (My University, 2022)
the detection of lumbosacral transitional vertebrae (LSTV) and vertebral enumeration. Patients and Methods: Institutional review board approval was obtained. Routine lumbar magnetic resonance (MR) imaging that included sagittal cervicothoracic scout images in 972 cases were evaluated retrospectively. Six segments were created in the vertebral column with 7 lines. CA and SMA ostiums were localized in these segments. Results: Coeliac artery and SMA levels were detected more caudally in lumbarized S1 and more cranially in sacralized L5 cases compared to non-LSTV cases. Conclusion: Coeliac artery and SMA origin levels as anatomical markers are not dependable for vertebral numbering due to their wide variability
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Lumbosacral transitional vertebrae; Coeliac artery; Superior mesenteric artery; Vertebral enumeration; Magnetic resonance imaging; PREVALENCE; CLASSIFICATION; ASSOCIATION; MRI; Lumbosacral transitional vertebrae; Coeliac artery; Superior mesenteric artery; Vertebral enumeration; Magnetic resonance imaging